2010
DOI: 10.1158/1078-0432.ccr-10-0054
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Phase I Dose-Escalation Study of Intratumoral Reovirus Type 3 Dearing and Palliative Radiotherapy in Patients with Advanced Cancers

Abstract: Purpose To determine the safety and feasibility of combining intratumoral reovirus and radiotherapy in patients with advanced cancer and to assess viral biodistribution, reoviral replication in tumors, and antiviral immune responses. Experimental Design Patients with measurable disease amenable to palliative radiotherapy were enrolled. In the first stage, patients received radiotherapy (20 Gy in five fractions) plus two intratumoral injections of RT3D at doses between 1 × 108 and 1 × 1010 TCID50. In the seco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 20 publications
2
65
0
Order By: Relevance
“…In addition, GL-ONC1 was investigated in combination with concurrent chemoradiotherapy for locally advanced head and neck cancer (i.e., against a highly toxic standard treatment backbone). We found that intravenous administration of GL-ONC1 was well tolerated in single and multiple escalating doses and was feasible in patients receiving standard chemoradiotherapy, which is consistent with the results of other clinical trials investigating oncolytic viruses (8,9,23,24). The results of this trial also suggest that GL-ONC1 may be a feasible treatment option with less toxic standard treatment approaches, such as concurrent radiation alone, or as monotherapy in a neoadjuvant or adjuvant treatment setting.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, GL-ONC1 was investigated in combination with concurrent chemoradiotherapy for locally advanced head and neck cancer (i.e., against a highly toxic standard treatment backbone). We found that intravenous administration of GL-ONC1 was well tolerated in single and multiple escalating doses and was feasible in patients receiving standard chemoradiotherapy, which is consistent with the results of other clinical trials investigating oncolytic viruses (8,9,23,24). The results of this trial also suggest that GL-ONC1 may be a feasible treatment option with less toxic standard treatment approaches, such as concurrent radiation alone, or as monotherapy in a neoadjuvant or adjuvant treatment setting.…”
Section: Discussionsupporting
confidence: 85%
“…28 Phase I clinical trials have already begun to explore the feasibility of combining oncolytic viruses with radiotherapy. [29][30][31] A clinical trial has also been undertaken to demonstrate the safety and feasibility of combining IR (single 5 Gy fraction) and oncolytic HSV-1 (JM Markert, personal communication). The data from the current study in part provided the basis for this trial in which radiotherapy is rationally integrated into the viral replicative cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, herpes simplex virus type 1 (OncoVEX GM-CSF ), reovirus (Reolysin) and vaccinia virus (JX-594) have all reached late-stage, randomised clinical trials either as single agent therapies or in combination with cytotoxic chemotherapy. In addition, recent studies have highlighted the fact that combining oncolytic virotherapy with ionizing radiation may lead to synergistic anti-tumor efficacy and translational phase I/II clinical trials have been completed (1,2). However, the reported complex effects of radiation on viral infectivity, replication, gene expression and cytotoxicity mean that detailed mechanistic preclinical studies are an essential prerequisite to trials of new oncolytic viral agents in combination with radiation.…”
Section: Introductionmentioning
confidence: 99%